PENGARUH PELATIHAN DAN PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN DI ELLENA SKIN CARE SOLO - Ismani Ismani; dasmadi Dasmadi; hari purwanto (EKOBIS, 2020)
Business opportunities for the world beauty business leaders, especially beauty clinics, the high need for beauty care makes a business opportunity for them. Beauty clinics compete with each other to show their competitive advantage through creative, innovative efforts, work effectively and efficiently so that the products and services they produce become choices for many customers. Based on the problem identification and problem limitation in this study, the problem was formulated whether the training and incentive had an effect on the performance of employees at Ellena Skin Care Solo?. This type of research based on its approach is quantitative research. This study uses a correlational design that is the relationship between independent variables X1, and X2 on the dependent variable Y. The population of this study is all employees of Ellena Skin Care Solo. The sampling technique in this study was total sampling, so the number of samples taken in this study were 30 respondents. This study uses a multiple linear regression data analysis approach. Based on the results of the study it is known that job training has a significant effect on employee performance, this is because Ellena Skin Care Solo is a company engaged in body and facial care services, so that every employee who works at Ellena Skin Care Solo always gets job training to provide supplies skills for employees in providing services to customers, so H1 is accepted. Incentives do not significantly influence the performance of Ellena Skin Care Solo employees, this is due to get incentives, employees are required to work with extra time or a larger portion of work, this is considered to provide incentives only as a substitute for fatigue, so H2 is rejected. Keywords : training, incentives, employee performance, Ellena Skin Care